Transformation of local wisdom values through the Merdeka Belajar principle in the Buru Island community - Waikabo, Ari Fandi; Samsuri (Jurnal Kependidikan: Penelitian Inovasi Pembelajaran, 2025)
The people of Wamlana Village believe that teaching based on local wisdom will support the character of the younger generation in the era of globalisation. This study aims to explore the values of local wisdom in a theoretical form converted into a form of practice by using the cycle of independent learning based on local wisdom for character building. The method used is a qualitative case study. This study uses interview guidelines, documentation and observation, analysis techniques in the form of data collection, data reduction, data presentation, and drawing conclusions. The results of the study found that the application of independent learning can (1) raise awareness of the preservation of local culture, (2) shape the character of students, (3) build local culture, and (4) strengthen identity.